Step-by-step explanation:
Below is an attachment containing the solution.
Local Max: x=3
Local Min: x=-9
Answer:
X = -8
Step-by-step explanation:
Answer:
a² + 4ab + 4b²
Step-by-step explanation:
Given
(a + 2b)²
= (a + 2b)(a + 2b)
Each term in the second factor is multiplied by each term in the first factor, that is
a(a + 2b) + 2b(a + 2b) ← distribute both parenthesis
= a² + 2ab + 2ab + 4b² ← collect like terms
= a² + 4ab + 4b²
Answer: 7.8 ⋅ ![10^{4}](https://tex.z-dn.net/?f=10%5E%7B4%7D)
Step-by-step explanation:
To write a linear expression in standard form, rearrange the terms in alphabetical order.
7.8 ⋅ ![10^{4}](https://tex.z-dn.net/?f=10%5E%7B4%7D)